Penerapan Strategi Attacking Dengan Metode Progresif Dalam Meningkatkan Keterampilan Bermain Untuk Mencetak Gol - Akmal Zain Islami; Asep Angga Permadi; Irwan Hermawan (Jurnal Porkes, 2026)
This study was motivated by the low effectiveness of the SMAN 15 Garut futsal team’s attacks, as reflected in a passing accuracy below 65%, a dribbling success rate of only 40–45%, and a goal tally of just 4–5 goals per match. The objective of this study was to analyze the effect of implementing an attacking strategy using a progressive method on improving playing skills to score goals. The method used was an experiment employing a True Experimental Design of the Pretest-Posttest Control Group type. The sample consisted of 28 students randomly divided into experimental and control groups. The intervention was administered over 8 weeks at a frequency of 3 times per week. Futsal skills were measured using the validated Games Performance Assessment Instrument (GPAI). The results showed that the experimental group experienced an average total increase of 23.3 percentage points (from 49.0% to 72.3%), while the control group increased by only 5.7 percentage points (from 46.0% to 51.7%). An Independent Samples t-test confirmed a highly significant difference (p < 0.001) with a Cohen’s d effect size of 1.84 (very large category). In conclusion, the implementation of an attacking strategy using a progressive method is highly effective in improving dribbling, passing, and shooting skills to score goals in the futsal games of students at SMAN 15 Garut.